Dynamic loading and linking native code on a real-time operating system. - Pierre-Alain Schäfer (2007)
This thesis presents a very efficient and simple approach to native code generation and dynamic code loading for the RTOS RTEMS on the Blackfin architecture. The whole solution is intended for PLCs implementing the IEC 61131-3 standard. The second part of the solution, native code loading on RTEMS, is also usable for code updates in satellite applications. For the code generation modern parser generator tools have been used to implement a language translator from Instruction List to C language. The generated C language is then feed to the freely distributable GCC compiler which generates efficient native code. This native code is later on loaded and executed on a Blackfin CPU. The execution environment RTEMS has been ported to the Blackfin architecture. RTEMS is a hard real-time operating system which has been widely used in space applications. For the dynamic loading and linking of the native code 2 different loaders have been evaluated and compared. Those loaders are of special interest for satellite applications because they allow for much faster software update over slow communication links. The final systems achieves a speedup of approximately 4 compared to a traditional interpreted IEC 61131-3 system.